PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS CANVA DENGAN MODEL ARTIKULASI PADA TEMA PERKEMBANGAN TEKNOLOGI - Rizal Anhari Naibaho (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This study aims to: (1) produce Canva-based learning video media on the theme of Technology Development in class III SD/MI. (2) determine the feasibility of Canva-based learning video media on the theme of Technology Development in class III SD/MI from the results of feasibility validation by material experts, media experts and learning experts. This research is a type of research and development with reference to the ADDIE model. The ADDIE model has stages, namely, Analyze (analysis), Design (design), Development (development), Implementation (application) and Evaluation (evaluation). The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. The developed media was validated by one material expert, one media expert and one learning expert. Validation by material experts was carried out in 2 stages and resulted in a product in the form of a Canva-based learning video media that was appropriate for third grade SD/MI students. . Validation by media experts was carried out in 2 stages and resulted in a product in the form of an appropriate learning video media for grade III SD/MI students. Validation by learning experts was carried out in 1 stage and resulted in a product in the form of an appropriate learning video media for grade III SD/MI students. Thus, the developed learning media is declared suitable for use in learning.